Air Extrusion System for Ionotropic Alginate Microgel Particle Formation: A Review. Issue 12 (13th October 2016) - Lee, Boon‐Beng; Bhandari, Bhesh R.; Howes, Tony
Abstract: Ionotropic alginate microgels are commonly used for bioencapsulation applications and the air extrusion system is one of the common methods employed to produce these microgels. Although there have been many individual studies, to date no single report has comprehensively summarized the findings and results of the usage of this system. This review gives insight into the air extrusion methods, covering the setup, type, and characteristics of the system, focusing on their innovative aspects. Characterization techniques for the resulting microgels are presented, along with the influence of process variables on the product size and the development of empirical models for size prediction. Abstract : Encapsulation can prolong the shelf life and improve/retain the quality of a product. The air extrusion system is commonly applied to produce ionotropic alginate microgels for bioencapsulation. The setup, design, and innovative aspects of the system as well as the techniques used to characterize microgels are explained. Empirical models for the size prediction of the microgels are summarized.